Pengaruh moderasi tax minimization terhadap debt covenant, ukuran perusahaan, dan keputusan transfer pricing - Maharani Putri Salsabila; I Gusti Ketut Agung Ulupui; Hafifah Nasution (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The purpose of this study was to analyze the effect of debt covenant and firm size on transfer pricing decisions with tax minimization as a moderating variable. Population of this study are consumer non-cyclicals companies listed on the Indonesia Stock Exchange during 2020-2022. The sample selection was carried out through purposive sampling technique where a total sample of 41 companies was obtained, with a total observation data of 123 data. This study used moderation regression analysis. The results proved that debt covenant and tax minimization have a positive effect on transfer pricing decisions while company size has a negative effect on transfer pricing decisions. The results also showed that tax minimization is able to moderate the effect of company size on transfer pricing decisions, but not able to moderate the effect of debt covenants on transfer pricing decisions.